Geografia, Riscos E Proteção Civil. Homenagem Ao Professor Doutor Luciano Lourenço. Volume 2 2021
DOI: 10.34037/978-989-9053-06-9_1.2_34
|View full text |Cite
|
Sign up to set email alerts
|

Perturbação de stress pós-traumático em bombeiros: prevenção e intervenção

Abstract: Os bombeiros, pela sua atuação em diversos contextos de risco, estão potencialmente expostos a situações propensas para o desenvolvimento da perturbação de stress pós-traumático (PTSD). Foi efetuada na EBSCO uma revisão da literatura sobre a prevenção e intervenção na PTSD, para identificar variáveis associadas e formas de prevenção e de intervenção, procurando, assim, sensibilizar para esta patologia e realçar a importância da saúde ocupacional dos b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The same evidence was found for firefighters after involvement in large-scale events (mean estimated prevalence of 12.3%) (Wagner et al, 2021b ). Evidence from other studies found prevalence rates of PTSD in firefighters between 1.9 and 57% (in contrast to 3.72–37.8% in the military workforce—for a review see Obuobi-Donkor et al, 2022 ), percentages between 6 and 48% (Vara et al, 2021 ), and Langtry et al ( 2021 ) cited 5–22%, while values in the general population from various countries vary between 1.3 and 3.5%, in contrast with the 10% prevalence found in rescue workers (Berger et al, 2012 ). Using the gold standard for measuring PTSD [Portuguese version of this instrument was develop by R. Ferreira, L. Ribeiro, P. Santos, and A. Maia in 2016 (Silva, 2018 ); the PTSD Checklist for DSM-5–PCL-5 scale (Weathers et al, 2013 )], Chiang et al ( 2021 ) found 21% with a probable diagnosis among a total of 164 professional firefighters, whereas Sun et al ( 2020 ) found 4.9% ( n = 409) and Shi et al ( 2021 ) found 1.9% ( n = 261) both within Chinese samples.…”
Section: Introductionmentioning
confidence: 97%
“…The same evidence was found for firefighters after involvement in large-scale events (mean estimated prevalence of 12.3%) (Wagner et al, 2021b ). Evidence from other studies found prevalence rates of PTSD in firefighters between 1.9 and 57% (in contrast to 3.72–37.8% in the military workforce—for a review see Obuobi-Donkor et al, 2022 ), percentages between 6 and 48% (Vara et al, 2021 ), and Langtry et al ( 2021 ) cited 5–22%, while values in the general population from various countries vary between 1.3 and 3.5%, in contrast with the 10% prevalence found in rescue workers (Berger et al, 2012 ). Using the gold standard for measuring PTSD [Portuguese version of this instrument was develop by R. Ferreira, L. Ribeiro, P. Santos, and A. Maia in 2016 (Silva, 2018 ); the PTSD Checklist for DSM-5–PCL-5 scale (Weathers et al, 2013 )], Chiang et al ( 2021 ) found 21% with a probable diagnosis among a total of 164 professional firefighters, whereas Sun et al ( 2020 ) found 4.9% ( n = 409) and Shi et al ( 2021 ) found 1.9% ( n = 261) both within Chinese samples.…”
Section: Introductionmentioning
confidence: 97%